CAMPUR KODE DAN ALIH KODE BAHASA JAWA-RIAU OLEH MASYARAKAT TRANSMIGRAN JAWA DI RIAU - Zuhri, Moh Sayful; Sumarwati, Sumarwati; Kurwidaria, Favorita (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2020)
This study aims to describe code mixing and code switching on the use of the Javanese language of the Riau transmigrant community. This study uses a qualitative descriptive research method. Data in the form of events in the form of speech acts using Javanese or mixed languages of other languages, as well as the existence of communication between O1 and O2, or the presence of a third party as O3, interviewing informants, and data in the form of documents. The data was obtained by using observation, interview, and recording techniques. The validity of the data is obtained by triangulation of theories, methods, and sources. The sampling technique used is purposive sampling. The data analysis technique used is an interactive analysis model, namely in the form of data reduction, data presentation, and drawing conclusions. The results of the study are as follows. The discovery of elements of the Riau language in the use of the Javanese language of the Riau transmigrant community. The mixed forms are in the form of phrases, clauses, idioms, basters and reduplications. As well as the language code shift, the code transition from Javanese to Riau Malay, Javanese to Indonesian, and Riau Malay to Javanese. The code switching occurs due to several factors and more internal types of code switching are found. As well as found deviations in the use of phonological, morphological, and lexicon types of language. This language mixing often occurs because of the multi-lingual environment, the language blends in, integrates between various regional languages. The level of speech that occurs shows the politeness in the environment.